The role of brand authenticity in activating brand love and brand trust and the implication on brand preference (brand study of the 2024 Indonesian presidential candidates) - Apriyana, Nurliya; Yuliana, Lingga; Alisia Putri Bestari; Tito Iswanto (Jurnal Ekonomi, 2024)
The study has examined the impact of brand authenticity in activating brand trust and brand love on brand preference in the 2024 presidential election. This research collected primary data by online questionnaire of 150 respondents were participated in the Indonesian presidential election of 2024. To prove empirically and validate the proposed model it tested by using partial least squares structural equation modelling (PLS-SEM). The findings indicate that presidential candidates brand authenticity have significant impacts on brand love, while presidential candidates brand authenticity have significant impacts on brand trust. Overall, presidential candidates brand love has significant impacts on brand preference, which in presidential candidate brand trust have significant impacts on brand preference. Finally, we find that the brand authenticity of presidential candidates serves as an electoral tool to build trust, love, and brand preference among voters.